Degradation of the Oxirane Ring of Epoxidized Vegetable Oils in Liquid-liquid Heterogeneous Reaction Systems - Campanella, Alejandrina (2006)
The reaction regimes under which proceed some of the relevant and deletereous consecutive reactions that occur during the conventional epoxidation process of vegetable oils were analyzed in detail, considering – separately – each transport and intrinsic kinetic step. Epoxidized soybean oil (ESBO) was used as a model material. In this process, peracetic acid is generated in situ by reacting acetic acid and H2O2 (aq) in a polar phase, so that the (acid catalyzed) reaction system is always heterogeneous. The distribution constants between the organic and the polar phases of soybean oil and ESBO were determined, as well as (in the case of the ring opening with acetic acid) the reaction rate constant in the homogeneous ESBO–glacial acetic acid reaction system. The epoxide ring opening caused by hydrogen peroxide is always slow and, unlike the attack by the acetic acid, progresses only in the polar phase. When no catalyst is added, the attack by acetic acid is also moderate, and the ring-opening reaction proceeds slowly in both phases, albeit slightly above the kinetic regime in the aqueous phase. However, if a homogeneous catalyst (e.g., sulfuric acid) is added, the reaction makes way in the instantaneous (mass-transfer controlled) regime in said phase.